One health approach to toxocariasis in Brazilian indigenous populations, their dogs, and soil contamination - Santarém, Vamilton Alvares; Doline, Fernando Rodrigo; Ferreira, Isabella Braghin; Farinhas, João Henrique; Biondo, Leandro Meneguelli; de Souza Filho, Roberto Teixeira; Pettan-Brewer, Christina; Giuffrida, Rogério; Lescano, Susana Angélica Zevallos; dos Santos, Andrea Pires; Kmetiuk, Louise Bach; Biondo, Alexander Welker (Frontiers in Public Health, 2023)
Introduction Although socioeconomic vulnerability and lifestyle factors may contribute to the transmission of Toxocara spp., no study has investigated indigenous populations in Brazil using the One Health approach. Methods Accordingly, this study assessed anti-Toxocara spp. antibodies in Brazilian indigenous people and healthcare professionals by enzyme-linked immunosorbent assay. Presence of Toxocara spp. eggs (feces and hair) in dogs as definitive hosts and in soil samples of the indigenous communities were also recovered and molecularly investigated. Results Overall, 342/463 (73.9%) indigenous individuals and 46/147 (31.3%) non-indigenous healthcare professionals were seropositive for Toxocara spp. In addition, T. canis eggs were retrieved from 9/194 (4.6%) dog fecal samples and 4/204 (2.0%) dog hair samples, mainly from the Paraná State communities (3/42; 7.1%). Soil contamination was observed only in the Paraná State communities (36/90; 40.0%), with the molecular detection of T. canis. River water consumption was also associated with indigenous seropositivity (Odds ratio, 11.4). Discussion Indigenous individuals in Paraná State communities were 2.72-fold more likely to be seropositive than those in São Paulo State, likely due to a lack of sanitary infrastructure. In this scenario, a primarily soil-transmitted disease may also have become waterborne, with embryonated eggs probably spread to water supplies by rain. Full-time healthcare professionals in daily contact with indigenous communities were 9.2-fold more likely to be seropositive than professionals who visited sporadically, suggesting exposure to Toxocara spp. during their work and raising health concerns. In addition, the findings herein showed a significantly higher seroprevalence in indigenous people than in healthcare workers (χ2 = 85.5; p < 0.0001), likely due to overtime exposure to Toxocara spp. In conclusion, Brazilian indigenous communities are highly exposed to toxocariasis, with poor infrastructure and contact with contaminated river water as associated risk factors and a higher risk of infection in healthcare professionals working full-time in these communities.